M.TAWMURATOV GÚRRIŃLERINIŃ IDEYALÍQ-TEMATIKALÍQ ÓZGESHELIKLERI - Kamalova, D. (SCIENCE and SOCIETY, 2024)
This article analyzes the ideological, thematic and compositional features of the stories of Marat Taumuratov, a famous representative of the prose genre in Karakalpak literature, using the examples of the works “Bizdi keshir, Gulnaz...” and “Khujdan khukmi”. This reveals the writer’s choice of topic and unique style.